Hubungan Gaya Belajar dengan Indeks Prestasi Semester Mahasiswa Prodi DIV Jurusan Kebidanan di Poltekkes Kemenkes Palu - Arie Maineny (Poltekkes Kemenkes Palu, 2019)
Every student has a different way of understanding and obtaning information. These differences can be influenced by learning styles. The calculation results based on the Grade Point Avarage (GPA) of the third-grade DIV Midwifery students showed that the GPA in each semester fluctuate, and the result of interviews most students used the method of learning with the rote system. This study was intended to know the correlation between learning styles with the GPA of the students. This study used an analytical survey method with a cross-sectional approach a stratified random sampling technique with 42 respondents, data analysis were done in univariate and bivariate using chi-square test. The results of the statistical test shows that the correlation between learning styles with the GPA was p-value 0,459. The most used learning style by respondents was auditory. The GPA category most owned by respondents was GPA ranges between 2,75 – 3,50 which was equal to 90,5%. The conclusion is that there was no correlation between of learning styles with GPA.